The SCUBA-2 Large eXtragalactic Survey: 850μm map, catalogue and the bright-end number counts of the XMM-LSS field. Issue 3 (30th January 2023) - Garratt, T K; Geach, J E; Tamura, Y; Coppin, K E K; Franco, M; Ao, Y; Chen, C -C; Cheng, C; Clements, D L; Dai, Y S; Dannerbauer, H; Greve, T R; et al.
ABSTRACT: We present $850\, μ {\rm m}$ imaging of the XMM -LSS field observed for 170 h as part of the James Clerk Maxwell Telescope SCUBA-2 Large eXtragalactic Survey (S2LXS). S2LXS XMM -LSS maps an area of $9\, {\rm deg}^2$, reaching a moderate depth of $1σ \simeq 4\, {\rm mJy\, beam^{-1}}$ . This is the largest contiguous area of extragalactic sky mapped by James Clerk Maxwell Telescope (JCMT) at $850\, μ {\rm m}$ to date. The wide area of the S2LXS XMM -LSS survey allows us to probe the ultra-bright ($S_{\rm 850μ m}\gtrsim 15\, {\rm mJy}$ ), yet rare submillimetre population. We present the S2LXS XMM -LSS catalogue, which comprises 40 sources detected at >5σ significance, with deboosted flux densities in the range of $7$ –$48\, {\rm mJy}$ . We robustly measure the bright-end of the $850\, μ {\rm m}$ number counts at flux densities ${\gt }7\, {\rm mJy}$, reducing the Poisson errors compared to existing measurements. The S2LXS XMM -LSS observed number counts show the characteristic upturn at bright fluxes, expected to be motivated by local sources of submillimetre emission and high-redshift strongly lensed galaxies. We find that the observed $850\, μ {\rm m}$ number counts are best reproduced by model predictions that include either strong lensing or source blending from a 15-arcsec beam, indicating that both may make an important contribution to the observed overabundance of bright single dish $850\, μ {\rm m}$ selected sources. We make the S2LXS XMM -LSS $850\, μ {\rm m}$ map and >5σ catalogue presented here publicly available.